Pengaruh Ketepatan Waktu, Kualitas Pelayanan, Dan Fasilitas Terhadap Kepuasan Konsumen Pada PT. Andry Febiola Transportasi Kabupaten Probolinggo (Jurusan Banyuwangi – Yogyakarta) - Rifan Firdaus; Mohammad Saiful Bahri; Khusnik Hudzafidah (CV. Ulil Albab Corp, 2026)
The purpose of this study is to examine the influence of punctuality, service quality, and facilities on customer satisfaction at PT. Andry Febiola Transportasi, Probolinggo Regency. This research method uses a quantitative research method with a causal relationship. The number of samples used was 150 respondents. Using the SmartPLS 4.0 application, which consists of two models, namely the evaluation of the measurement model (outer model) and the evaluation of the structural model (inner model). The results of the study are as follows: 1). Punctuality has a significant effect on customer satisfaction at PT. Andry Febiola Transportasi, Probolinggo Regency. 2). Service quality has a significant effect on customer satisfaction at PT. Andry Febiola Transportasi, Probolinggo Regency. 3). Facilities have a significant effect on customer satisfaction at PT. Andry Febiola Transportasi, Probolinggo Regency.